Integration of Guidance and Counseling in Supporting Early Childhood Mental Health in the Implementation of the Independent Curriculum - Fifi Khoirul Fitriyah; Berda Asmara; Asmaul Lutfauziah; Muhammad Syaikhon; Halida Halida (UNUSA Press, 2026)
The implementation of the Independent Curriculum in Early Childhood Education (PAUD) units requires a learning approach that is oriented not only towards academic achievement and character, but also towards children's mental health and psychosocial well-being. In this context, the integration of guidance and counseling services is a strategic element to support the holistic development of early childhood. This study aims to analyze the form of guidance and counseling integration in the implementation of the Independent Curriculum at Anak Ceria PAUD and its impact on early childhood mental health. This study used a descriptive qualitative approach. Data were collected through participatory observation of 20 early childhood children, semi-structured interviews with 5 PAUD teachers and 2 principals, and analysis of learning documents and child development records. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and techniques. The results show that guidance and counseling at Anak Ceria PAUD are contextually integrated within play-based learning and the Independent Curriculum project. This integration has a positive impact on emotional regulation, healthy social interactions, independence, and children's sense of safety in the school environment, which are important indicators of mental health and psychosocial well-being in early childhood. Teachers act as developmental counselors through emotional support, positive reinforcement, and empathetic interactions, although this is not supported by a structured formal guidance and counseling program. This study concludes that the integration of guidance and counseling is an effective promotive and preventive effort in supporting early childhood mental health and strengthening the implementation of the Independent Curriculum in early childhood education units.